Cu/CeO2 Catalyst for Water‐Gas Shift Reaction: Effect of CeO2 Pretreatment. Issue 12 (17th April 2018) - Chen, Chongqi; Zhan, Yingying; Zhou, Jianke; Li, Dalin; Zhang, Yanjie; Lin, Xingyi; Jiang, Lilong; Zheng, Qi
Abstract: CuO/CeO2 is a kind of promising catalysts for the water‐gas shift (WGS) reaction. Efforts were put in to improve its performance through modification of CeO2 support. In this study, portions of CeO2 prepared by a co‐precipitation method were separately annealed at 300 °C in air, under vacuum and with H2, and were used as supports for the fabrication of CuO/CeO2 catalysts. The physicochemical properties of the catalysts were characterized by X‐ray diffraction, N2 ‐physisorption, inductively coupled plasma, Raman spectroscopy, CO2 temperature‐programmed desorption, and H2 temperature‐programmed reduction techniques. The relation between catalytic performances and physicochemical properties of the CuO/CeO2 catalysts were discussed. Among the three catalysts, the one with CuO supported on H2 ‐reduced CeO2 shows the highest catalytic activity, mainly due to strong CuO‐CeO2 synergetic interaction and high concentration of Frenkel‐type oxygen vacancies. The superior catalytic activities can also be attributed to the Cu 0 crystals of small size and the oxygen vacancies in non‐stoichiometric CeO2‐ x . Abstract : One type or another : Both Frenkel‐type oxygen vacancy and the one generated from non‐stoichiometric CeO2‐ x are responsible for the enhanced catalytic activity of CuO‐CeO2 catalyst in the water‐gas shift reaction.